2019
DOI: 10.3348/kjr.2019.0140
|View full text |Cite
|
Sign up to set email alerts
|

2018 Korean Liver Cancer Association–National Cancer Center Korea Practice Guidelines for the Management of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the fifth most common cancer globally and the fourth most common cancer in men in Korea, where the prevalence of chronic hepatitis B infection is high in middle-aged and elderly patients. These practice guidelines will provide useful and constructive advice for the clinical management of patients with HCC. A total of 44 experts in hepatology, oncology, surgery, radiology, and radiation oncology in the Korean Liver Cancer Association-National Cancer Center Korea Practice Guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
134
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(135 citation statements)
references
References 714 publications
(887 reference statements)
1
134
0
Order By: Relevance
“…However, CEUS is not recommended as a primary imaging modality by the leading hepatology societies. 6,7,45,46 Except for the American Association for the Study of Liver Diseases, CEUS is regarded as a secondary imaging option.…”
Section: Discussionmentioning
confidence: 99%
“…However, CEUS is not recommended as a primary imaging modality by the leading hepatology societies. 6,7,45,46 Except for the American Association for the Study of Liver Diseases, CEUS is regarded as a secondary imaging option.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging is important in HCC screening, surveillance, diagnosis, staging, and management ( 2 3 4 ). Clinical practice guidelines, including those of the Association for the Study of Liver Disease (AASLD) ( 1 ), European Association for the Study of the Liver (EASL) ( 5 ), and the Korean Liver Cancer Association and National Cancer Center (KLCA-NCC) ( 6 ), recommend contrast-enhanced CT and MRI for HCC diagnosis ( 7 ). However, these guidelines differ regarding the use of contrast-enhanced ultrasound (CEUS) for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have found that when considering the arterial phase hyper-enhancement pattern and the onset and intensity of washout, CEUS did well on distinguishing HCC from OM [ 7 , 8 ]. In recognition of the usefulness of CEUS, several guidelines recommended it as the first- or second-line tool [ 9 , 10 , 11 , 12 ]. The CEUS LI-RADS was first introduced in 2016 for trial implementation and it was officially issued in 2017 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%